Synchrotron nano-FTIR spectroscopy for probing anticancer drugs at subcellular scale - de Carvalho, LAEB; Cinque, G; de Carvalho, ALMB; Marques, J; Frogley, MD; Vondracek, H; Marques, MPM (Nature Research, 2024)
The cellular response to cisplatin was assessed in human osteosarcoma cells, using synchrotron-based (SR) Fourier Transform InfraRed nanospectroscopy (nano-FTIR) at the MIRIAM beamline B22 of Diamond Light Source (UK). This label-free mapping method delivered simultaneous morphological and biochemical information on a subcellular level (i.e. 100 s nanometer or better). Based on specific spectral biomarkers, the main biochemical constituents affected by the drug were identified at distinct locations within the cell´s inner body. Cisplatin was shown to have a noteworthy effect on proteins, mostly within the cytoplasm. A clear drug impact on cellular lipids was also observed. Within current literature on s-SNOM, this nanospectroscopy work represents a first successful application in life sciences providing full fingerprint nano-FTIR spectra across intact human cancer cells.